IMPLEMENTATION OF KAIZEN TO REDUCE SETUP AND ADJUSTMENT DOWNTIME ON ROTOR PRODUCTS WITH THE DMAIC METHOD - Zamzam Zaelani, Mohamad; Kholil, Muhammad (Yayasan Nuraini Ibrahim Mandiri, 2025)
In the industrial sector, production process efficiency plays a crucial role in reducing costs and enhancing productivity. This study aims to minimize downtime caused by Setting tool activities on the Rotor machining 5A OP 20 line at an air compressor manufacturing company. The approach combines the continuous improvement philosophy of Kaizen with the structured DMAIC (Define, Measure, Analyze, Improve, Control) methodology from Six Sigma. Data revealed that Setting tool activities contributed to 3.08% of total downtime, exceeding the company's target of 2.00%. Through primary and secondary data collection and quantitative analysis, this research identified several root causes, including suboptimal tool lifetime, inappropriate Cutting Parameters, and the absence of standardized operating procedures. Interventions were carried out by improving tool specifications, developing SOPs, conducting operator training, and visualizing production data. As a result, downtime was reduced by 27.7%, tool lifetime increased by 10%, and estimated Cost Savings reached IDR 41,654,021 .81 per year. Beyond technical achievements, the study demonstrates that cross-functional collaboration and active employee involvement in the Improvement process foster a more efficient, adaptive, and sustainable work culture. The integration of Kaizen principles supported by the DMAIC framework proves to be an effective strategy for enhancing operational efficiency and achieving comprehensive cost reduction in the manufacturing sector.